Putting a halt to unnecessary transfers: Do patients with isolated subarachnoid hemorrhage and Glasgow Coma Scale of 13 to 15 need a trauma center?. Issue 1 (July 2020) - Sharma, Jyoti; Defoe, Danielle; Gillen, Jenna; Kuo, Yen-Hong; Perez, Javier; Dalal, Setu; Dayal, Saraswati; Kiselak, Elizabeth; Rippey, Kelly; Kaul, Sanjeev; Cohn, Stephen
Abstract : OBJECTIVES: Trauma patients with isolated subarachnoid hemorrhage (iSAH) presenting to nontrauma centers are typically transferred to an institution with neurosurgical availability. However, recent studies suggest that iSAH is a benign clinical entity with an excellent prognosis. This investigation aims to evaluate the neurosurgical outcomes of traumatic iSAH with Glasgow Coma Scale (GCS) of 13 to 15 who were transferred to a higher level of care. METHODS: The American College of Surgeon Trauma Quality Improvement Program was retrospectively analyzed from 2010 to 2015 for transferred patients 16 years and older with blunt trauma, iSAH, and GCS of 13 or greater. Those with any other body region Abbreviated Injury Scale of 3 or greater, positive or unknown alcohol/drug status, and requiring mechanical ventilation were excluded. The primary outcome was need for neurosurgical intervention (i.e., intracranial monitor or craniotomy/craniectomy). RESULTS: A total of 11, 380 patients with blunt trauma, iSAH, and GCS of 13 to 15 were transferred to an American College of Surgeon level I/II from 2010 to 2015. These patients were 65 years and older (median, 72 [interquartile range (IQR), 59–81]) and white (83%) and had one or more comorbidities (72%). Eighteen percent reported a bleeding diathesis/chronic anticoagulation on admission. Most patients had fallen (80%), had a GCS of 15 (84%), and were mildly injured (median Injury Severity Score, 9 [IQR, 5–14]). Only 1.7% required neurosurgical intervention with 55% of patients being admitted to the intensive care unit for a median of 2 days (IQR, 1–3 days). Furthermore, 2.2% of the patients died. The median hospital length of stay was only 3 days (IQR, 2–5 days), and the most common discharge location was home with self-care (62%). Patient factors favoring neurosurgical intervention included high Injury Severity Score, low GCS, and chronic anticoagulation. CONCLUSION: Trauma patients transferred for iSAH with GCS of 13 to 15 are at very low risk for requiring neurosurgical intervention. LEVEL OF EVIDENCE: Therapeutic/care management, Level IV.